Bi-allelic variants in COL3A1 encoding the ligand to GPR56 are associated with cobblestone-like cortical malformation, white matter changes and cerebellar cysts. Issue 6 (3rd March 2017) - Vandervore, Laura; Stouffs, Katrien; Tanyalçin, Ibrahim; Vanderhasselt, Tim; Roelens, Filip; Holder-Espinasse, Muriel; Jørgensen, Agnete; Pepin, Melanie G; Petit, Florence; Khau Van Kien, Philippe; Bahi-Buisson, Nadia; Lissens, Willy; et al.
Abstract : Background: Collagens are one of the major constituents of the pial membrane, which plays a crucial role in neuronal migration and cortical lamination during brain development. Type III procollagen, the chains of which are encoded by COL3A1, is the ligand of the G protein-coupled receptor 56 (GPR56), also known as adhesion G protein-coupled receptor G1. Bi-allelic mutations in GPR56 give rise to cobblestone-like malformation, white matter changes and cerebellar dysplasia. This report shows that bi-allelic mutations in COL3A1 are associated with a similar phenotype. Methods: Exome analysis was performed in a family consisting of two affected and two non-affected siblings. Brain imaging studies of this family and of two previously reported individuals with bi-allelic mutations in COL3A1 were reviewed. Functional assays were performed on dermal fibroblasts. Results: Exome analysis revealed a novel homozygous variant c.145C>G (p.Pro49Ala) in exon 2 of COL3A1 . Brain MRI in the affected siblings as well as in the two previously reported individuals with bi-allelic COL3A1 mutations showed a brain phenotype similar to that associated with mutations in GPR56 . Conclusion: Homozygous or compound heterozygous mutations in COL3A1 are associated with cobblestone-like malformation in all three families reported to date. The variability of the phenotype across patients suggests that genetic alterations in distinct domains of type III procollagen can lead to different outcomes. The presence of cobblestone-like malformation in patients with bi-allelic COL3A1 mutations emphasises the critical role of the type III collagen–GPR56 axis and the pial membrane in the regulation of brain development and cortical lamination.